A network approach to assessing cognition in disorders of consciousness [Image: see text] [Image: see text] - Rodriguez Moreno, D. (American Academy of Neurology, 2010)
OBJECTIVE: Conventional assessments of consciousness rely on motor responses to indicate awareness. However, overt behaviors may be absent or ambiguous in patients with disorders of consciousness (DOC) resulting in underrating capacity for cognition. fMRI during a silent picture-naming task was evaluated as an indicator of command following when conventional methods are not sufficient. METHODS: A total of 10 patients with and without conventional evidence of awareness, who met diagnostic criteria for the minimally conscious state (MCS) (n = 5), vegetative state (VS) (n = 3), emerged from MCS (EMCS) (n = 1), and locked-in syndrome (LIS) (n = 1), participated in this observational fMRI study. RESULTS: The LIS and EMCS patients engaged a complete network of essential language-related regions during the object-naming task. The MCS and 2 of the VS patients demonstrated both complete and partial preservation of the object-naming system. Patients who engaged a complete network scored highest on the Coma Recovery Scale-Revised. CONCLUSIONS: This study supports the view that fMRI during object naming can elicit brain activations in patients with DOC similar to those observed in healthy subjects during command following, and patients can be stratified by completeness of the engaged neural system. These results suggest that activity of the language network may serve as an indicator of high-level cognition and possibly volitional processes that cannot be discerned through conventional behavioral assessment alone. GLOSSARY: BA: = Brodmann area; BOLD: = blood oxygenation level–dependent; CRS-R: = Coma Recovery Scale-Revised; DOC: = disorders of consciousness; EMCS: = emerged from minimally conscious state; GFi(d): = dorsal inferior frontal gyrus; GFi(v): = ventral inferior frontal gyrus; hrf: = hemodynamic response function; LIS: = locked-in syndrome; MCS: = minimally conscious state; preSMA: = pre-supplementary motor area; STG: = superior temporal gyrus; VS: = vegetative state.